Bahasa Inggris - Emeline Aime Kandiawan; Delia Layandi; Gracielle Febriana Benly; Felicia Wong; Tiffany Thesagita; Mustika Kusuma Basir; Afrizal Firman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
This study examines the impact of discounts and product bundling on impulsive buying behavior among consumers in Makassar City. Primary data were collected through an online survey using Google Forms with a quantitative approach. The survey collected responses from 80 frequent e-commerce platform users. This research investigates how discounts and product bundling affect impulsive buying. Structural Equation Modeling-Partial Least Squares (SEM-PLS) is used to analyze the data. The results show that there is a strong positive relationship between Discount and Impulsive Buying. Product Bundling showed a negative link with Impulsive Buying, which is different from what was found in previous studies. This indicates that the people who answered the survey see value perception, high prices, and limited flexibility as obstacles to emotional appeal, which usually encourages people to make purchases on impulsive. As a result, this study suggests that there is a negative link between product bundling and impulsive buying.